Building Physics as a Tool for Development of New Components: Roof Window. (August 2019) - Tywoniak, J; Calta, V; Staněk, K; Novák, J; Maierová, L
Abstract: Knowledge and instruments of building physics (calculation methods and measuring procedures) can be used as key tools and perspectives to develop new components for building envelopes. This paper illustrates this fact by presenting the successful development of a roof window fulfilling higher requirements on reduction of overall heat losses and avoiding the risk of water vapor condensation on surfaces at very low external temperatures (thermal transmittance below 0.7 W/m 2 K in the first generation, close to 0.5 W/m 2 K in the second one) and better daylight distribution for the interior. This is the result of a publicly supported project with an industrial partner: from a general idea through detailed analysis of thermal performance in geometrical and material alternatives up to construction, prototyping, and verification by measurements and certification. Building physics tools applied in the project are discussed here together with lessons learned which are important for technical design. An effective shading system equipped with PV elements for energy smart harvesting is mentioned in the conclusion.